Rapid ground subsidence in the Kucuk Menderes Graben (W. Turkey) captured by Sentinel-1 SAR data - Imamoglu, Mumin; Balik Sanli, Fusun; Cakir, Ziyadin; Kahraman, Fatih (SPRINGER, 2022)
Over the past few decades, surface deformations have been observed and measured geodetically at many places all over the world, including Central and western Turkey. Surface deformations in some of these regions have been attributed to aseismic slip-on faults and/or to excessive pumping of groundwater. In this study, we present our investigation on the ground subsidence in odemis town (W. Turkey) located in the Kucuk (K.) Menderes Graben where one of the most severe and widespread surface fracturings has been reported. The entire graben is analyzed using the Sentinel-1 synthetic aperture radar (SAR) data with multi-temporal interferometric SAR techniques. A total of 342 single look complex products acquired in 2015-2018 are processed using the Small Baseline Subset method. Vertical mean velocity fields reveal that K. Menderes Graben is experiencing extensive subsidence at rates reaching as much as 29 cm/year, making it one of the fastest subsiding regions in the world. The spatial correlation between the subsiding regions and the unconsolidated sediments suggests that the subsidence is most probably due to over drafting of the groundwater, which is confirmed by the strong temporal correlation between displacement time series and groundwater level changes. Inelastic/elastic deformation ratios calculated for the entire graben suggest that inelastic deformation is the dominant component in the region, implying an irreversible deformation. Skeletal storage coefficients calculated at well locations also support the idea of inelastic deformation. However, severe inelasticity is not extensive, and the region may still recover from subsidence with correct groundwater management.
Keywords: InSAR time series; Sentinel-1; Land subsidence; Kucuk Menderes Graben; Western Turkey; TIME-SERIES ANALYSIS; SMALL BASE-LINE; RIVER-BASIN; DEFORMATION; INSAR; VALLEY; INTERFEROMETRY; DISPLACEMENTS; ANATOLIA; RECHARGE; Environmental Sciences & Ecology; Geology; Water Resources